Aspiration-Induced Acute Lung Injury: Experimental Morphological Study - A. M Golubev; Yu. A. Gorodovikova; V. V. Moroz; Yu. V Marchenkov; D. V. Sundukov (Общая реаниматология)
Objective: to reveal early lung morphological changes after acidin-pepsin aspiration (a combination of hydrochloric acid and proteolytic enzyme). Material and methods. An experiment was made on 30 non-inbred albino male rats whose trachea acidin-pepsin solution (pH 1.2) was administered into. The experiment lasted 1 to 24 hours. Lung histological specimens were stained with hematoxylin and eosin. Results. After an hour of surgery, all the animals developed interstitial edema, had the desquamated bronchial epithelium, segmented leukocytic infiltration of alveolar septa, hemorrhages, and sludges. Conclusion. Acidin-pepsin aspiration leads to the development of acute lung injury verified by morphological studies. Key words: aspiration, acute lung lesion.